Age influence on quality of shell and penetration in bacterial laying lightweight eggs - Smaniotto, B. D. [UNESP] (2017)
This study evaluated the influence of the bird's age on the quality of the shell and percentage of bacterial penetration in commercial eggs. White-shelled commercial eggs were used, laid by light laying hens in their first laying cycle at 21, 39, 51, and 62 weeks of age. Shell quality evaluations comprised: egg weight, specific gravity, percentage and thickness of shell, number and size of pores. For evaluations regarding bacterial penetration, strains of several enterobacterias and one salmonella were used, all of which resistant to Nalidixic acid (100μg/ml). The method employed for evaluation of bacterial penetration was filling the eggs with growth medium. The data were subjected to variance analysis with 5% of probability using SAS (Education Analytical Software, 2013). Eveb though increase in the laying hen's age caused reduction of the quality of eggshells, it failed to affect the percentage of penetration of the bacterial samples evaluated.